Scandals of Reason - Literature and Theology in Jorge Luis Borges’s “La otra muerte” - Lucas Martín Adur Nobile (Teoliterária: Revista Brasileira de Literaturas e Teologias, 2015)
Borges’s definition of theology as “una parte de la literatura fantástica” has been quoted countless times as an example of borgesian scepticism. Nevertheless, the various relationships which Borges establishes between literature and theology are more complex than this apothegm may lead us to think. This article examines the ways in which Borges’s short story “La otra muerte” interrelates theological and literary discourses. We will focus especially in two procedures. In the first place, this article will analyze how Borges establishes an intertextual relationship between “La otra muerte” and several literary as well as theological works, which leads to a blurring of genres. On the other hand, this paper will examine what I call Borges’ “theology - fiction”: a peculiarly borgesian, literary approach to theological issues, and one with surprising investigative and doctrinal capacity.